Identifikasi Dini Guna Mengoptimalkan Kemampuan Bahasa pada Anak Tuna Rungu Usia Pra Sekolah - HarwantiNoviandari; Agus Mursidi (Ilmu Psikologi Universitas Yudharta Pasuruan)
Language skills are needed by children in communicating with others, so the child needs to create their language that is verbal leaguage and sign language to send their message. Limited hearing function in deaf children, making them unable to hear well.This condition make the deaf children unable to have experience in communicating and interacting with their social environment.This research uses a descriptive qualitative approach.The selection of respondents using snow ball technique, where the sample is an expert that are undertanding about what we are expect.Those who know (an expert) about the condition of child in school, is :school principal, class teacher at the Banyuwangi District PAUD Institution.Based on the results of research conducted at 17 PAUD Institutions in Banyuwangi Districtthere are children who experience delays in speaking at 10 PAUD Institutions in Banyuwangi District.The research also showed that only SPS Cerdas found children with hearing loss (deaf child).That need attention including : (1) The importance of the role of parents in optimizing language skills in children; (2) The importance of establishing a two-way communication between parents and the school to make conditions in children more better;(3) Public awareness of not understanding the tasks of children in their developmental stages, (4) The role of government is needed in completing medical facilities for children with special conditions.